Magnetization and specific heat of La doped Sr2FeMoO6 - Tovar, M.; Sereni, J.G.; Pedrazzini, P.; Caneiro, A.; Prado, F.; Butera, A.; Causa, M.T.; Sereni, Julián; Pedrazzini, Pablo (Elsevier, 2004)
Fil: Tovar, M. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina